Electronic Tutorials: Indonesian experience - Belawati, Tian; Anggoro, Mohamad Toha; Hardhono, A.P.; Darmayanti, Tri (International Review of Research in Open and Distributed Learning, 2002)
As in other developing nations, important concerns surrounding education in Indonesia involve two issues: quantity versus quality. Quality concerns have now been somewhat addressed by the establishment of the Indonesian Open Learning University (Universitas Terbuka) in 1984. The concern for quality, however, has not yet been completely resolved. Learning support, believed to be key for achieving good quality distance education, has been limited. This paper presents the results of two pilot projects that examined tutorials provided via Internet and Fax-Internet technologies. It is a report that also shows that the Universitas Terbuka is faced with both visible and invisible challenges. Visible challenges include limitations in the availability of technology infrastructure and issues of inadequate access, while invisible challenges include the readiness of Indonesian people to adopt and take advantage of new technology for educational purposes. Despite the results of the pilot project, it is suggested that Universitas Terbuka should continue to utilize Internet and Fax-Internet as two of its communication channels with students.